An Efficient Methodology Based on Coverage Area to Modify Location and Power Ratings of Distribution Transformers - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2021)
The Technology development and rising standards of living are increasing the demand for electricity in city centres. In addition, the density of electric power in different areas of a city changes with the construction of new residential areas. Variation in load density can be managed by adjusting the voltage on distribution lines, installing new lines and transformer centres, and reconfiguring existing lines and transformer centres. In this study, the Istanbul Uskudar District of Kanlica-Cubuklu Region was examined and coverage areas were modified depending on the load density and power of the existing transformers. A novel systematic approach to determine the coverage area of transformers is presented. In this approach, the coverage area and overlap of each transformer with its neighbours were determined. Subsequently, transformers that are under-used or have significant overlap with neighbouring transformers were removed from the network. The transformers were placed into an optimal structure in the network by distributing the load of an excluded transformer to its nearest neighbours. This approach further allows the minimum route for the high voltage distribution wiring between transformers and cost to be determined.
Keywords: Substations; Distribution networks; Planning; Urban areas; Optimization; Sociology; Statistics; Coverage area; distribution network planning; distribution transformer; load density; optimization; substation determination; DISTRIBUTION-SYSTEM; DISTRIBUTION SUBSTATION; MODEL